Step by step, building a virtual exchange program between five european universities - Redchuk, Andrés (2011)
It is commonly claimed that the Exchange program ERASMUS (European Action Scheme for the Mobility of University Students) can be regarded as one of the biggest successes of the European Union (EU) educational policy in the past years. Since its launching in 1987, more than 3,000,000 students and teachers have participated in their programmes. However, the majority of the participants have been undergraduate students, being the presence of postgraduate students merely testimonial (something that the Bologna Process aims at changing). One of the main reason for this phenomenon may be that, as more mature people, postgraduate students might have more restrictive family, professional and/or work ties. With this motivation in mind, we proposed the EU our VRTUOSI project, www.vrtuosi.org, within the Virtual Campus methodological framework of the EU Lifelong Learning Programme (LLP). Ours was one of the five proposals chosen by the EU in the 2009 announcement. On the other hand, quality is an important issue within the European educational framework, as only outstanding programs will benefit from European and national funds and will call attention of a larger number of students, ensuring their survival in a very competitive environment. In this regard, we provide details of the design, development and implementation of a Six-Sigma-based methodology to assess the quality in our Master degrees. This quality management system was first implemented in our Decision Systems Engineering Master (DSEM). In this work, we provide a detailed description of the VRTUOSI program, putting special emphasis on its more paradigmatic issues, which might be of interest to other Higher Educational Institutions planning to implement similar programmes. We describe here the organization and implementation of VRTUOSI, a pioneer virtual exchange program between five European universities, we present our six sigma based methodology designed and developed to improve quality in it. We describe its structure and implementation through the web and its application to improve the European e-learning program and the online Master in Decision Systems Engineering. We describe its positive effects on internationalization of our online Masters.